FEATURES OF TAXATION AND TAX ACCOUNTING IN BUDGETARY INSTITUTIONS OF UKRAINE - LAGODIIENKO, Nataliia; IVANCHENKOVA, Larysa; FURSA, Victoriia; SKLIAR, Larysa; YEVTUSHEVSKA, Olha (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article provides a comprehensive analysis of the taxation system applicable to budgetary institutions in Ukraine, focusing on the organizational principles of tax accounting and reporting within these public entities. It outlines the unique operational characteristics of budgetary institutions that have a direct impact on their tax obligations and financial practices. The study identifies the types of taxes that such institutions are legally required to withhold, calculate, and remit, including personal income tax, military levy, unified social contribution (USC), environmental tax, property tax, transport tax, land tax, and value-added tax (VAT). Emphasis is placed on the legal framework governing each of these taxes, particularly highlighting the procedural aspects of determining tax liabilities, calculating tax bases, and ensuring compliance with statutory requirements. Special attention is devoted to the peculiarities of VAT accounting in budgetary institutions, including the identification of taxable transactions, applicable tax rates, the process of recognizing tax obligations and input VAT credits, and the documentation required to substantiate tax positions. Furthermore, the article delves into the accounting treatment of various taxes within the financial systems of budgetary institutions, analyzing how these taxes are recorded and reported in alignment with public sector accounting standards. The structure and content of tax reporting are also examined in detail, including the specific forms and schedules mandated for fiscal reporting. The findings of the article have practical implications for administrators and financial officers of Ukrainian budgetary institutions, offering guidance for establishing efficient and compliant tax accounting systems that support the transparent and lawful use of public resources. By improving tax reporting accuracy and compliance, these institutions can enhance fiscal discipline and accountability within the public administration framework.